Reduced-dimensional MPC controller for direct thrust control - Pang, Shuwei; Jafari, Soheil; Nikolaidis, Theoklis; Li, Qiuhong (Elsevier, 2021)
With the development of the aircraft gas turbine engine, a control system should be able to achieve effective thrust control to gain better operability. The main contribution of this paper is to develop a novel direct thrust control approach based on an improved model predictive control method through a strategy that reduces the dimension of control sequence. It can not only achieve normal direct thrust control tasks but also maximize the thrust level within the safe operation boundaries. Only the action of switching the objective functions is required to achieve the switch of these two thrust control modes while there is no modification to the control structure. Besides, a shorter control sequence is defined for multivariable control by updating only one control variable at every simulation time instant. Therefore, the time requirement for the solving process of the optimal control sequence is reduced. The proposed controller is implemented to a twin-spool engine. Simulations are conducted in the wide flight envelope, and results show that the average time-consumption can be reduced up to 65% in comparison with the standard model predictive control, and the thrust can be increased significantly when maximum thrust mode is implemented by using engine limit margins.
Keywords: Computation time; Direct thrust control; Gas turbine engine; Model predictive control; Thrust optimization